In situ observations of a possible skate nursery off the western Antarctic Peninsula. Issue 6 (20th April 2015) - Amsler, M. O.; Smith, K. E.; McClintock, J. B.; Singh, H.; Thatje, S.; Vos, S. C.; Brothers, C. J.; Brown, A.; Ellis, D.; Anderson, J.; Aronson, R. B.
<x xml:space="preserve">Abstract</x> A dense aggregation of skate egg cases was imaged during a photographic survey of the sea floor along the western Antarctic Peninsula in November 2013. Egg cases were noted in a narrow band between 394 and 443 m depth. Although some skate species in other oceans are known to utilize restricted areas to deposit eggs in great numbers, such nurseries have not been described in the Southern Ocean.